2020
DOI: 10.1155/2020/3105874
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Continuous Paravertebral Block after Minimally Invasive Radical Esophagectomy for Esophageal Cancer

Abstract: Objective. To compare the effects of continuous paravertebral block analgesia and patient-controlled intravenous analgesia after minimally invasive radical esophagectomy for esophageal cancer and their effects on postoperative recovery. Methods. A retrospective analysis was performed among 233 patients who underwent minimally invasive esophageal cancer radical operation and met the requirements, including 87 patients (group C) who were successfully placed with a continuous paravertebral block device under dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, the requirements for ultrasound imaging and block technology are high, the operation space is limited and the difficulty is greater, the success rate is low. There is a possibility of puncturing the pleura and damaging the intercostal nerve or sympathetic chain [8,21,23,24]. Compared with TPB, erector spinae plane block has a higher success rate, but requires higher ultrasound imaging and block technique [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, the requirements for ultrasound imaging and block technology are high, the operation space is limited and the difficulty is greater, the success rate is low. There is a possibility of puncturing the pleura and damaging the intercostal nerve or sympathetic chain [8,21,23,24]. Compared with TPB, erector spinae plane block has a higher success rate, but requires higher ultrasound imaging and block technique [19].…”
Section: Discussionmentioning
confidence: 99%
“…The second method is to place the catheter in the paravertebral space through percutaneous puncture outside the pleura under thoracoscopic direct vision, this can achieve a similar continuous block as the catheter placed under ultrasound guidance. TPB can effectively reduce both the postoperative pain and consumption of opioids after thoracic surgery [7,24,26,27]. Both TPBs require at least three to five minutes during the procedure, possibly longer if the action is not smooth.…”
Section: Discussionmentioning
confidence: 99%
“…Regional analgesia techniques seem to be effective in postoperative management. Zhang et al reported that continuous paravertebral block alleviated the pain of patients in the resting and active state for patients undergoing MIE, which enabled patients to get out of bed early, cough and sputum effectively, and decreased the incidence of pulmonary complications [7]. Postoperative pain in MIE mainly comes from the trauma of thoracic and abdomen, especially originated from the upper abdominal incision [15].…”
Section: Discussionmentioning
confidence: 99%
“…Ideal postoperative analgesia contributes to the patient's cough and expectoration, and would decrease complications such as hypoxemia, atelectasis, and pulmonary infection. Zhang et al reported that continuous paravertebral block analgesia increased the satisfaction of postoperative analgesia and decreased the incidence of pulmonary complications for patients undergoing minimally invasive esophagectomy (MIE) [7]. However, Brovman found that the regional anesthetic techniques were not associated with a lower incidence of pulmonary complications in lobectomy surgery [8].…”
Section: Introductionmentioning
confidence: 99%